Elucidation of fluorine's impact on pKa and in vitro Pgp-mediated efflux for a series of PDE9 inhibitors. Issue 5 (2nd May 2018) - Fjelbye, Kasper; Marigo, Mauro; Clausen, Rasmus P.; Jørgensen, Erling B.; Christoffersen, Claus T.; Juhl, Karsten
Abstract : The influence of replacing a hydrogen atom with fluorine on the p K a and Pgp-mediated efflux is elucidated for a series of PDE9 inhibitors. Abstract : P-Glycoprotein (Pgp)-mediated cellular efflux is recognized as a common challenge in CNS drug discovery. In this study, the influence of replacing a hydrogen atom with fluorine on the p K a and Pgp-mediated efflux is elucidated for a series of PDE9 inhibitors. The PDE9 inhibitors with and without fluorine were synthesized using a novel condensation–oxidation approach, providing access to several analogues, all from the same stereoenriched aldehyde building block. The incorporation of fluorine was found to influence two acid–base functionalities concomitantly, both of which were involved in Pgp-recognition. By methylating the acidic functionality, it was possible to isolate the effect responsible for lowering the Pgp-mediated efflux.